2020
DOI: 10.1162/jocn_a_01521
|View full text |Cite
|
Sign up to set email alerts
|

The Causal Role of Left and Right Superior Temporal Gyri in Speech Perception in Noise: A Transcranial Magnetic Stimulation Study

Abstract: Successful perception of speech in everyday listening conditions requires effective listening strategies to overcome common acoustic distortions, such as background noise. Convergent evidence from neuroimaging and clinical studies identify activation within the temporal lobes as key to successful speech perception. However, current neurobiological models disagree on whether the left temporal lobe is sufficient for successful speech perception or whether bilateral processing is required. We addressed this issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 58 publications
3
15
0
Order By: Relevance
“…In addition, superior frontal and temporal regions are engaged in lip reading, although we did not find strong evidence for a modality preference of these regions. None of these comprehension-relevant regions was strictly lateralised, in line with the notion that speech comprehension is largely a bilateral process ( Kennedy-Higgins et al, 2020 ).…”
Section: Discussionsupporting
confidence: 75%
“…In addition, superior frontal and temporal regions are engaged in lip reading, although we did not find strong evidence for a modality preference of these regions. None of these comprehension-relevant regions was strictly lateralised, in line with the notion that speech comprehension is largely a bilateral process ( Kennedy-Higgins et al, 2020 ).…”
Section: Discussionsupporting
confidence: 75%
“…right superior temporal regions were interrupted in healthy participants (Kennedy-Higgins et al 2020).…”
Section: Right Hemisphere Resultsmentioning
confidence: 96%
“…At least one study (Boatman et al, 1998) (Wada & Rasmussen, 1960), and functional neuroimaging studies of speech perception routinely implicate right temporal structures in speech perception (Belin, Zatorre, Hoge, Evans, & Pike, 1999;Blumstein, Myers, & Rissman, 2005;Davis, Ford, Kherif, & Johnsrude, 2011;Giraud et al, 2004;Turkeltaub & Branch Coslett, 2010;Zatorre, Meyer, Gjedde, & Evans, 1996). More recently, a study by Kennedy-Higgins, Devlin, Nuttall, and Adank (2020) found that listeners' ability to repeat speech presented against background noise was impaired when they received TMS above either the left or right superior temporal gyrus, but not when stimulation was performed at a control site. Collectively, such findings suggest a non-negligible role for the right hemisphere in speech perception.…”
Section: How Might the Right Hemisphere Support Speech Perception?mentioning
confidence: 99%